Realization of a historical map from seventeenth century - Almarri, Ali; Al-Bedwawi, Saif (Al-Adab Journal, 2023)
The map industry in Europe flourished during expeditions to the East in order to gain access to spices and control main navigation routes. This led to a widespread interest in the science and production of maps, as each country sought to acquire its own sources of information about newly discovered areas and ways to reach them. Maps containing rare or exclusive information were particularly valuable during this period and are still considered highly sought after. The current study presents a brief overview of the historical features of maps by the renowned geographer Ptolemy, followed by the cartographer Gastaldi who introduced a more realistic style of cartography. The research specifically focuses on a German map, titled in Arabic, dating back to 1681 and created by the engineer Manson Mallet for his published works. An analysis of all the names mentioned on the map was conducted, as well as the accompanying decorations which were widespread on most European geographical maps during that period.The analysis found several names that were common in the Arabian Peninsula, including the division of the peninsula into parts, naming the Arabian Gulf after the Gulf of Persia and Bahrain, and maintaining the name of the Red Sea. Additionally, the importance of the Arabian Peninsula and Mesopotamia during this period was emphasized and maps of this region were carefully preserved. This analysis may provide a broader perspective for making comparisons between maps of the region, and more information can be obtained about the Arabian Peninsula and its surrounding areas according to the historical period to which these maps belong.